Safety and efficacy of mechanical thrombectomy with stent-retrievers in anticoagulated patients with anterior circulation stroke - Krajíčková, D; Krajina, A; Herzig, R; Vítková, Eva; Halúsková, S; Vyšata, O; Čabelková, P; Vališ, M (Clinical radiology, 2019)
AIM: To assess the safety and efficacy of mechanical thrombectomy (MT) with stent-retrievers in anterior circulation stroke (ACS) patients due to the occlusion of major cerebral arteries, and to compare the results achieved in patients on oral anticoagulation (OAC) and those not on OAC. MATERIALS AND METHODS: The present retrospective study comprised 285 consecutive patients (115 males; mean age 74±13 years). The following data were collected: baseline characteristics, occurrence of risk factors, pre-event treatment with OAC, neurological deficit at the time of treatment, time to therapy, recanalisation rate (successful recanalisation defined as Thrombolysis in Cerebral Infarction score ≥2b), post-treatment imaging findings. The 90-day clinical outcome was assessed using modified Rankin scale (good outcome defined as 0-2). RESULTS: The following statistically insignificant differences were found in 26 patients on OAC versus 259 patients without OAC: occurrence of symptomatic intracerebral haemorrhage 7.7% versus 8.1%, achievement of successful recanalisation 69.2% versus 82.6%, good 90-day clinical outcome 34.6% versus 56.8%, 90-day mortality 26.9% versus 20.8% (p>0.05 in all cases). Age and neurological deficit at the time of treatment were identified as independent negative predictors of good 90-day clinical outcome (odds ratio [OR]=0.90, 95% confidence interval [CI]: 0.88-0.94 and OR=0.83, 95% CI: 0.77-0.90, respectively) and as independent positive predictors of mortality (OR=1.12, 95% CI: 1.06-1.18 and, OR=1.17, 95% CI: 1.07-1.27, respectively; p<0.05 in all cases). CONCLUSIONS: MT with stent-retrievers is safe and effective in ACS patients on OAC.
Keywords: dospělí; Cerebral Arteries; cévní mozková příhoda; senioři nad 80 let; Tomography, X-Ray Computed; trombektomie; retrospektivní studie; Humans; lidé středního věku; Cohort Studies; Aged, 80 and over; Middle Aged; Young Adult; mladý dospělý; stenty; Brain Ischemia; mužské pohlaví; Age Factors; Stroke; Adult; Adolescent; výsledek terapie; digitální subtrakční angiografie; Stents; Treatment Outcome; ischemie mozku; ženské pohlaví; věkové faktory; lidé; mladiství; antikoagulancia; Anticoagulants; kohortové studie; počítačová rentgenová tomografie; Aged; senioři; Male; Retrospective Studies; Thrombectomy; arteriae cerebrales; Angiography, Digital Subtraction; Female